FORENSIC ODONTOLOGY IN THE ERA OF PRECISION FORENSICS: LANDMARK CASES, DISASTER VICTIM IDENTIFICATION, AND EMERGING DIGITAL TECHNOLOGIES (Asian Journal of Medical Research and Health Sciences, 2026)
What was once considered a subspecialty of dentistry has evolved to become a major arm of forensic science. As dental structures are extremely durable and of extreme individuality, they can provide vital information for the identification of human remains when all other evidence has been exhausted. This article looks back at the history of odontology through key events and case studies that have made an impact in the subject. It then goes on to look at how evidence can be provided for the estimation of age and sex, for the use of bite marks as evidence, for DNA profiling from dental remains, and for post-mortem identification from dental records. It then goes on to highlight the areas where the subject is performing well and those where it is struggling. The article also looks at the current trends that will impact practice in the future, including the use of cone-beam computed tomography (CBCT) and three-dimensional reconstructions. It also goes on to discuss the impact that digital dentistry, artificial intelligence, machine learning, radiomics, and even molecular biomarkers will have on the current practice of odontology for forensic purposes. The article also discusses the current challenges that odontological evidence is facing from an ethical and legal perspective and how these can be addressed by adopting standardized protocols and by adopting an interdisciplinary approach. The history of the subject is discussed and brought up to date on current trends and how the subject is being used in the role of the subject in the pursuit of justice and in humanitarian identification, and how it is at the forefront of the new era of precision forensic science.